Digital tools for delivery of dementia education for health-care providers: a systematic review. Issue 11 (2nd November 2019) - Scerbe, A.; O'Connell, M. E.; Astell, A.; Morgan, D.; Kosteniuk, J.; DesRoches, A.
ABSTRACT: Continuing education on dementia for health-care providers has been shown to have positive effects on diagnostic confidence, knowledge, and care management. Technological approaches to educational delivery have been found to have comparable effects in terms of quality and efficacy. The purpose of the systematic review was to compose and present an evidence base for technology-delivered dementia education for health-care providers. The review used PRISMA guidelines and Cochrane methods focusing on studies with a pre- and post-intervention evaluation. Technology-based delivery of dementia education was broadly defined as any technology-based medium delivered in real time or asynchronously. Ten studies were identified and analyzed using content analysis. The review revealed positive outcomes post-intervention, for dementia knowledge, readiness to change, receptiveness to training, communication skills, and self-efficacy. Studies were rated as medium to high quality on a scale for measurement of published data in research, and there was generally an unknown risk of bias due to a lack of a control group in most studies ( N = 7). The findings revealed benefits of digitally-based, asynchronous continuing education for health-care providers, which allow schedule flexibility and the ability to deliver remotely. Findings also revealed benefits of presentations using a variety of interactive educational materials via videos, voice recordings, textual medium and online discussion groups. Suggestions for intervention improvements include tailoring training for the specific needs and knowledge levels of health-care practitioners and using validated scales to measure outcomes.